ONLINE AND BLENDED LEARNING MODELS: A COMPREHENSIVE ANALYSIS - Azamjonova Muqaddaskhan (Bright Mind Publishing, 2025)
This article explores the increasing role of online and blended learning in modern education. It provides a detailed analysis of how these models affect academic performance, student engagement, and teaching practices. Through literature review, surveys, and case studies, the study compares the strengths and weaknesses of both online and blended models. Online learning offers flexibility and wider access, particularly during emergencies like the COVID-19 pandemic. However, it also presents challenges such as low motivation, reduced interaction, and digital inequality. Blended learning, on the other hand, combines face-to-face instruction with digital tools, promoting higher student engagement and better academic outcomes. The article also discusses the importance of teacher training, student support, and investment in technology infrastructure. The findings suggest that while neither model is perfect, blended learning offers a balanced and sustainable approach to future education. The results are relevant for school leaders, policymakers, educators, and students aiming to improve learning experiences in the digital age.
Keywords: Blended learning, Online education, Student engagement, Digital tools, Academic performance, Educational equity, Teacher training, Motivation, E-learning, Digital infrastructure.